Sambiloto (AS201-01) is better than standard antimalarial drug (DHP) in reducing Toll-Like Receptor 2 (TLR2) on placenta malaria model - Masyitah Hamidah; Aty Widyawaruyanti; Widjiati Widjiati; Budi Prasetyo (Majalah Obstetri dan Ginekologi, 2018)
Objectives: To compare the TLR2 expression in the placenta between treated by sambiloto EA-96 fraction tablet (AS201-01) and dihydroartemisinin-piperaquine phosphate (DHP)Materials and Methods: Experimental study using 24 pregnant mice. All sample divided into 4 groups with randomization are uninfected group, Plasmodium infected group and given placebo, sambiloto (AS201-01) and DHP. Then performed surgery and placental sampling were staining with adopting in tunnel assay method to measure the TLR2 expression of placental.Results: The expression of TLR2 in uninfected group has the lowest rate compared to other groups. The infected and placebo treated group has the highest TLR2 expression campared with sambiloto and DHP. The sambiloto group has not differ signi-ficantly with the group uninfected and lower than DHP.Conclusion: Tablet of sambiloto EA-96 fraction (AS201-01) decreased TLR2 expession better than with DHP tablet.